Risk factors for readmission in patients discharged with outpatient parenteral antimicrobial therapy: a retrospective cohort study - Victoria Huang (BMC Pharmacology and Toxicology, 2018)
Abstract Background Outpatient parenteral antimicrobial therapy (OPAT) is a practical and effective way of delivering antimicrobial therapy, but may be associated with significant risk for hospital readmission. This study aimed to elucidate risk factors related to 30-day readmissions in patients who were discharged with OPAT at Mount Sinai Beth Israel (MSBI). Methods This IRB approved retrospective cohort study included patients who were at least 18 years or older, admitted to MSBI from August 2015 to March 2016, and discharged to receive OPAT. Patients with intravenous antibiotics prescribed for chronic suppression or planned readmission within 30 days were excluded. The main outcome was readmission to the hospital within 30 days from previous hospital discharge. Univariate and logistic regression analyses were performed to determine predictors of 30-day readmission. Results There were a total of 200 patients included in the analysis; the median age was 60 years, 65.5% were male, and the median Charlson score was 2. A total of 155 (78%) patients received a peripherally inserted central catheter (PICC); the remainder was discharged with a midline. The most common medications prescribed for OPAT included cephalosporins (41%), vancomycin (31%), carbapenems (23%), and penicillins (16%). A total of 42 patients (21%) were readmitted within 30 days after previous discharge. Discharge to a skilled nursing facility or subacute rehabilitation center was found to be an independent predictor of readmission on logistic regression analyses (p <  0.05). Conclusion Readmissions are common in patients discharged with OPAT. Recognizing predictors of readmission may help determine strategies to optimize care.